A Independência da Escolha dos Canais de Marketing nas Rendas dos Produtores Orgânicos Americanos2 - Scalco, Andréa Rossi [UNESP]; Souza, Roberta; Campos-silva, Willerson Lucas; Baker, Gregory (Sociedade Brasileira de Economia e Sociologia Rural, 2017)
One of the issues related to strategies for capturing value in organic production activities is the decision regarding the appropriate product distribution channel. The literature points out the importance of analyzing the gains of organic small producers concerning the marketing channels for organic products. Research indicates that marketing through direct channels is an advantage for small producers since these channels promote increased value capture and, consequently, increased income. Empirical research was conducted in California, United States, in which 60 organic producers were surveyed to determine whether direct distribution is the preferred type of distribution channel utilized by small producers. The results indicate that the choice of distribution channel, direct or indirect, and the type of channel within this category, is not directly related to producer income. There are indications that the choice of the appropriate channel is more connected to producers’ motives, quality of life, and perspectives on the growth of their business. Moreover, diversification of marketing channels may be an important mechanism to reduce the risks involved in the marketing their products.

Uma das atividades relacionadas às estratégias de captura valor na atividade produtiva de orgânico refere-se à escolha dos canais adequados de distribuição dos produtos. A literatura aponta a importância de analisar os ganhos dos pequenos produtores com respeito aos canais de distribuição de produtos orgânicos. A literatura indica que a comercialização em canais diretos pode fazer com que pequenos produtores possam capturar maior valor e, consequentemente, incrementar sua renda. Foi realizada uma pesquisa empírica no estado da Califórnia, nos Estados Unidos da América, por meio de um survey com 60 produtores de orgânicos, a fim de identificar se os canais de distribuição diretos são prioritariamente utilizados por pequenos produtores. Os resultados indicam que a escolha dos canais de distribuição, venda direta ou indireta, além do tipo de canal dentro dessa categorização, não está diretamente relacionado apenas à renda que o produtor pode obter. Há indicações de que a escolha do canal adequado esteja mais relacionada às motivações do produtor rural, em relação à qualidade de vida e perspectivas de crescimento do seu negócio, além da opção pela diversificação dos canais para diminuir os riscos envolvidos na comercialização de seus produtos.
Keywords: distribution channels; value capture; organic; canais de distribuição; valor; orgânico